Constrained patterning of orientated metal chalcogenide nanowires and their growth mechanism - Qishuo Yang; Yun-Peng Wang; Xiao-Lei Shi; XingXing Li; Erding Zhao; Zhi-Gang Chen; Jin Zou; Kai Leng; Yongqing Cai; Liang Zhu; Sokrates T. Pantelides; Junhao Lin (Nature Communications, 2024)
Abstract One-dimensional metallic transition-metal chalcogenide nanowires (TMC-NWs) hold promise for interconnecting devices built on two-dimensional (2D) transition-metal dichalcogenides, but only isotropic growth has so far been demonstrated. Here we show the direct patterning of highly oriented Mo6Te6 NWs in 2D molybdenum ditelluride (MoTe2) using graphite as confined encapsulation layers under external stimuli. The atomic structural transition is studied through in-situ electrical biasing the fabricated heterostructure in a scanning transmission electron microscope. Atomic resolution high-angle annular dark-field STEM images reveal that the conversion of Mo6Te6 NWs from MoTe2 occurs only along specific directions. Combined with first-principles calculations, we attribute the oriented growth to the local Joule-heating induced by electrical bias near the interface of the graphite-MoTe2 heterostructure and the confinement effect generated by graphite. Using the same strategy, we fabricate oriented NWs confined in graphite as lateral contact electrodes in the 2H-MoTe2 FET, achieving a low Schottky barrier of 11.5 meV, and low contact resistance of 43.7 Ω µm at the metal-NW interface. Our work introduces possible approaches to fabricate oriented NWs for interconnections in flexible 2D nanoelectronics through direct metal phase patterning.